Kaiser and Führer : a Comparative Study of Personality and Politics. - Waite, Robert G. L. (University of Toronto Press, 1998)
Thoroughly documented and engagingly written this is a classic work of scholarship that will fascinate historians, psychologists, and general readers alike.